2017
DOI: 10.26501/jibm/2017.0701-010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance Index and Earnings Management on Firms’ Performance: A Comparative Study on the Islamic Versus Conventional Financial Institutions in Pakistan

Abstract: Abstract. This study investigates the impact of corporate governance index and earnings management on firms' performance and makes a comparative analysis of the selected Islamic and conventional financial institutions in Pakistan for the period of [2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015]. Data of 20 KSE listed Islamic financial institutions (i.e., a few Islamic banks and mostly mud .ā rabah companies), and 35 KSE listed conventional financial institutions (i.e., conventional banks, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Concerning CG, EM and performance relationship, Abbadi et al (2016) reported that EM is negatively affected by overall CGQ index categories in Jordan. Ashfaq et al (2017) also reported that the CG index has a significant positive impact on firms’ performance for conventional and Islamic financial institutions. Their findings indicate that, as CGQ improves, its ability to constrain EM also improves, leading to performance enhancements in firms.…”
Section: Methodsmentioning
confidence: 97%
“…Concerning CG, EM and performance relationship, Abbadi et al (2016) reported that EM is negatively affected by overall CGQ index categories in Jordan. Ashfaq et al (2017) also reported that the CG index has a significant positive impact on firms’ performance for conventional and Islamic financial institutions. Their findings indicate that, as CGQ improves, its ability to constrain EM also improves, leading to performance enhancements in firms.…”
Section: Methodsmentioning
confidence: 97%
“…The most used theory during the period of 2002-2020 is the agency theory, which is used in 65% of this review study. Agency theory has been adopted in 52 studies which are quantitative in nature, linking it with firm performance [28,47,67,94,118,130,138] typically the researcher tried to link it with confit of interest hypothesis which arises due to separation of ownership and control [43,72]. Additionally, the agency theory has been applied to the topics of earnings management [19,42,63,73,75,89,107] and financial reporting quality [119,129] to check the board of directors monitoring and controlling role over the companies' management.…”
Section: Theoretical Underpinning and Linked Theoriesmentioning
confidence: 99%
“…In Islamic banks, the information asymmetry creates moral hazard problems related to agency theory when there is a high ratio of deposits in the banks. This calls for governance reforms in Islamic banks (Ashfaq et al, 2017). Therefore this study will analyze the previous literature in a critical and systematic way to ascertain if Islamic banks are distributing profits in a realistic manner or there are some anomalies in the PLS paradigm of Islamic banks.…”
Section: Problem Statementmentioning
confidence: 99%
“…PLS principle asserts that the real profits earned must be shared between the parties involved. Still, the Islamic banks offer profits which indicate profit distribution management (PDM) (Farook, Hassan, & Lanis, 2011;Abdul-rahman & Nor, 2016;Ashfaq et al, 2017;Chowdhury, Shoyeb, Akbar, & Islam, 2017). PDM is an ex post effect of the intermediary function performed by Islamic banks (Taktak, 2014;Farook, Hassan & Clinch, 2012;Siswantoro, 2017;Wafaretta, Rosidi, & Rahman, 2016;Hamza 2016).…”
Section: Introductionmentioning
confidence: 99%